INTERVENSI AKTOR DALAM MEMPENGARUHI FORMULASI KEBIJAKAAN PENDIDIKAN: STUDI KASUS PENDIRIAN SEKOLAH MENENGAH ATAS NEGERI CILONGOK - Saputra, Anggara Setya; Suryoto, Suryoto; Agustina, Alfriansa; Widyaningsih, Faulia (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The Zoning Policy is the main step and strategy in accelerating the equitable distribution of education and the development of quality learning in schools to welcome the progress of the implementation of planned programs in the field of education to the community. This makes the Zoning Policy process one of the efforts to realize the improvement of the education system which is taken by the general path systematically by the government and educational institutions in improving learning in the world of education in maintaining the balance of the government towards the lives of the people of the nation and state. This research was conducted using exploratory case studies. This research uses a descriptive approach based on the formulation form process in this is a policy from the High School Zoning Policy in Banyumas Regency The collection of data for this research through the process of interviews, observations and documentation. The selection of information is carried out by purposive sampling technique. The informants were selected by purposive sampling according to the purpose of the study. The results showed that in the process of formulating the upper school zoning policy, it was very influential as this system had been implemented in building education in Banyumas Regency, but this was not in accordance with reality. This happens because in one sub-district of Banyumas Regency there is a sub-district that has no access, services or educational facilities, namely Cilongok District. The process of developing alternative options for high school zoning policies in Banyumas Regency It is also necessary to note the ability of involvement of each actor in the development process because it greatly affects the running of the high school zoning policy in Banyumas Regency in accordance with the expectations desired by the government for equitable distribution of education and improvement of the education system based on the zoning system.